Outer Electrospun Polycaprolactone Shell Induces Massive Foreign Body Reaction and Impairs Axonal Regeneration through 3D Multichannel Chitosan Nerve Guides. (9th April 2014) - Duda, Sven; Dreyer, Lutz; Behrens, Peter; Wienecke, Soenke; Chakradeo, Tanmay; Glasmacher, Birgit; Haastert-Talini, Kirsten
Abstract : We report on the performance of composite nerve grafts with an inner 3D multichannel porous chitosan core and an outer electrospun polycaprolactone shell. The inner chitosan core provided multiple guidance channels for regrowing axons. To analyze the in vivo properties of the bare chitosan cores, we separately implanted them into an epineural sheath. The effects of both graft types on structural and functional regeneration across a 10 mm rat sciatic nerve gap were compared to autologous nerve transplantation (ANT). The mechanical biomaterial properties and the immunological impact of the grafts were assessed with histological techniques before and after transplantation in vivo . Furthermore during a 13-week examination period functional tests and electrophysiological recordings were performed and supplemented by nerve morphometry. The sheathing of the chitosan core with a polycaprolactone shell induced massive foreign body reaction and impairment of nerve regeneration. Although the isolated novel chitosan core did allow regeneration of axons in a similar size distribution as the ANT, the ANT was superior in terms of functional regeneration. We conclude that an outer polycaprolactone shell should not be used for the purpose of bioartificial nerve grafting, while 3D multichannel porous chitosan cores could be candidate scaffolds for structured nerve grafts.